ESTIMASI NILAI EKONOMI TOTAL (TOTAL ECONOMIC VALUE) SUMBERDAYA ALAM DAN LINGKUNGAN DANAU SINGKARAK - Idris Idris (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractLake Singkarak is one of natural resources and environmental which is important for human life. Itis located in West Sumatera Province, with area of 11220 km2 and 136 m depth. Until 2000, therewere no studies about the total economic value of lake Singkarak resource. That is the reasonwhy the researcher wants to conduct a research to estimate the use value and non-use valueof it. In order to quantify the value above, he used some approaches that based on theconcept of individual willingness to pay, by using the framework of the total economic value.The study shows that total economic value of natural resources and environmental of Singkaraklake is Rp. 174.950 billion per year. It consists of (a) the economic value of fishery Rp. 7,328billion, (b) the economic value of irrigation Rp. 0, 775 billion, (c) the economic value ofrecreation Rp. 4,176 billion, (d) the economic value of domestic use Rp. 7,718 billion, and (e)the the economic value of electricity power Rp. 154,992 billion. These findings are usefull forthe government as the policy maker to manage the development of lake Singkarak’s naturalresources and its environmental efectively and sustainability.